(untitled) (Indian Journal of Child Health, 2025)
Background: Acute Gastroenteritis is considered to be a major cause of morbidity and mortality among children all around the globe. Annually, 3 to 5 billion cases of Acute Gastroenteritis are reported from all over the world and it is estimated to be responsible for 2 million deaths among children below 5 years of age. Methods: An observational descriptive study with a cross-sectional design was conducted at the pediatric department of North Bengal Medical College and Hospital. The sample size was calculated using the Cochrane formula using the prevalence of the outcome in the population. The patients admitted to the study institution with clinically diagnosed acute gastroenteritis were selected by a consecutive sampling technique till the required sample size was reached. At the time of admission, the sociodemographic details of the patients were obtained from their parents using a predesigned questionnaire. After that, blood was drawn from the patients to measure serum haemoglobin, sodium, potassium, and calcium. Results: Out of 160 children, most of the children were between 49-60 months with male predominance born out of Spontaneous Vaginal Delivery; mothers were young and resided in rural areas. Exclusive breastfeeding was not practised, improper administration or lack of Oral Rehydration Solution contributed to the high prevalence of electrolyte abnormality. Conclusions: The study concludes that there is an urgent need for effective educational interventions to improve ORS administration and breastfeeding practices, especially in rural areas. Enhancing caregiver knowledge and public health strategies could substantially reduce the incidence of electrolyte disturbances and improve clinical outcomes for children with acute gastroenteritis.